2004
DOI: 10.1111/j.1471-4159.2004.02513.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of neurohybrid cell death induced by Alzheimer's amyloid‐β peptides via p75NTR/PLAIDD

Abstract: One of the most important pathological features of Alzheimer's disease (AD) is extracellular senile plaques, whose major component is amyloid-b peptides (Ab). Ab binds to the extracellular domain of p75NTR (p75 neurotrophin receptor) and induces neuronal cell death. We investigated the molecular mechanism of Ab-induced neurotoxicity in detail from the standpoint of interaction between p75NTR and its recently identified relative, PLAIDD (p75-like apoptosis-inducing death domain). Using F11 neuronal hybrid cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 60 publications
(72 reference statements)
3
50
0
1
Order By: Relevance
“…2 In this study, using specific ligands for p75NTR, we were able to induce apoptosis, thus counteracting the survival effects mediated by Trk. Indeed, b-amyloid specifically binds p75NTR and induces apoptosis only in keratinocytes expressing p75NTR, similarly to b-amyloid peptide-induced cell death in Alzheimer's neuronal cells 31 and in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…2 In this study, using specific ligands for p75NTR, we were able to induce apoptosis, thus counteracting the survival effects mediated by Trk. Indeed, b-amyloid specifically binds p75NTR and induces apoptosis only in keratinocytes expressing p75NTR, similarly to b-amyloid peptide-induced cell death in Alzheimer's neuronal cells 31 and in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several potential death-mediating receptors for toxic A â have been reported (27). In addition, p75NTR and/or PLAIDD, putative cell membrane receptors for Aâ, are able to cause neuronal cell death when ectopically overexpressed (18,44). We have recently demonstrated that TGF â2 is a natural ligand for amyloid-precursor protein (APP) that activates a neuronal cell death signal cascade (20).…”
Section: Neuronal-death Mechanismsmentioning
confidence: 99%
“…Several reports have suggested that activation of tyrosine kinases may play a role in A␤-induced neuronal death (12,13) or may have a neuroprotective function, as was shown for nicotinic receptor-dependent Jak2 kinase activation, which is induced by nicotine, but not A␤, binding to the receptor (14). Some other putative A␤ receptors are thought to signal through G proteins (5,15), which might implicate tyrosine kinase activity in downstream signaling (reviewed in ref. 16), although the kinase substrates functionally involved in A␤ toxicity are not known.…”
mentioning
confidence: 99%